2005
DOI: 10.1080/08958370590885690
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Adult Mice to Environmental Tobacco Smoke Fails to Enhance the Immune Response to Inhaled Antigen

Abstract: Epidemiologic evidence supports a role for environmental tobacco smoke (ETS) in the occurrence and severity of allergies/asthma. However, neither the precise combination of ETS and allergen exposure nor the mechanism (or mechanisms) by which these factors interact and contribute to asthma induction is known. Animal model studies have failed to establish a convincing relationship between ETS exposure and asthma induction, perhaps because of methodological inadequacies. Here, we tested the hypothesis that ETS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Although several prior studies examining ETS exposure in combination with allergen exposure in mice have demonstrated enhanced Th2 responses (17, 18, 28 -30), other studies have demonstrated that the combination of ETS exposure and OVA allergen can inhibit Th2 responses and AHR (31)(32)(33). The differences in the results in these studies may be due to differences in ETS and OVA exposure protocols, differences in exposure to mainstream smoke vs ETS, as well as differences in timing of ETS exposure during the sensitization compared with the allergen challenge period.…”
Section: Discussionmentioning
confidence: 99%
“…Although several prior studies examining ETS exposure in combination with allergen exposure in mice have demonstrated enhanced Th2 responses (17, 18, 28 -30), other studies have demonstrated that the combination of ETS exposure and OVA allergen can inhibit Th2 responses and AHR (31)(32)(33). The differences in the results in these studies may be due to differences in ETS and OVA exposure protocols, differences in exposure to mainstream smoke vs ETS, as well as differences in timing of ETS exposure during the sensitization compared with the allergen challenge period.…”
Section: Discussionmentioning
confidence: 99%
“…For smoke inhalation, sidestream smoke comprised approximately 90% of SHS, and the remaining 10% consisted of exhaled mainstream smoke (32)(33)(34). Here, sidestream smoke served as a surrogate for SHS (32)(33)(34).…”
Section: Shs Exposurementioning
confidence: 99%
“…However, not all studies supported a positive contribution of cigarette smoke exposure to the allergic phenotype and sensitization phenomenon, possibly as a result from the variable experimental conditions used among different laboratories (e.g., the use of environmental vs mainstream smoke, whole-body vs nose-only exposure, etc.) (11,12,14,15). One outstanding observation was that the effects of smoke exposure on allergic responses appear to be dose dependent (15).…”
mentioning
confidence: 99%